2009
DOI: 10.1111/j.1744-7917.2009.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a cerebral factor showing summer‐morph‐producing hormone activity in the brain of the seasonal non‐polyphenic butterflies Vanessa cardui, V. indica and Nymphalis xanthomelas japonica (Lepidoptera: Nymphalidae)

Abstract: Presence of a cerebral factor showing summer-morphproducing hormone activity in the brain of the seasonal nonpolyphenic butterflies Vanessa cardui, V. indica and Nymphalis xanthomelas japonica (Lepidoptera: Nymphalidae) Abstract Three species of nymphalid butterflies, Vanessa cardui, V. indica and Nymphalis xanthomelas japonica, do not exhibit seasonal polyphenism in wing coloration. To determine whether seasonal non-polyphenic butterflies possess a cerebral factor affecting wing coloration, we used a Polygoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Recently, a cerebral factor showing SMPH activity was detected in pupal brain‐extracts of the non‐polyphenic nymphalid butterflies V. cardui , V. indica and N . xanthomelas japonica using a Polygonia pupal assay, suggesting that a cerebral factor showing SMPH activity (or a SMPH) may be distributed widely in many species of butterflies (Tanaka et al, ). It is therefore necessary to investigate the detection of a cerebral factor showing SMPH‐activity in the pupal brain of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a cerebral factor showing SMPH activity was detected in pupal brain‐extracts of the non‐polyphenic nymphalid butterflies V. cardui , V. indica and N . xanthomelas japonica using a Polygonia pupal assay, suggesting that a cerebral factor showing SMPH activity (or a SMPH) may be distributed widely in many species of butterflies (Tanaka et al, ). It is therefore necessary to investigate the detection of a cerebral factor showing SMPH‐activity in the pupal brain of A .…”
Section: Discussionmentioning
confidence: 99%
“…c‐aureum and P. xuthus , and SMPH activity is detectable using a Polygonia female SD‐pupal assay and a Papilio chilled‐male SD‐pupal assay (Endo et al, ; Ito et al, ). Recently, we also reported that a cerebral factor showing SMPH activity was detected in pupal brain‐extracts of Vanessa cardui , V. indica , and Nymphalis xanthomelas japonica , which do not exhibit seasonal polyphenism, using a Polygonia female SD‐pupal assay, although the roles of the cerebral factor showing SMPH activity have not been studied in these butterflies (Tanaka et al, ). Overall observations suggest that a cerebral factor showing SMPH activity is distributed in the pupal brains of many nymphalid butterflies.…”
mentioning
confidence: 99%
“…; Tanaka et al . ), we first detected this factor in the larval brains of four Papilio species in this work. These results revealed that a cerebral factor showing SMPH activity is already synthesized in the 5th larval stage, suggesting that this factor acts not only on the seasonal morph development in adults, but also on the unknown seasonal or phenotypic plasticity in larvae, if this factor is present in the young instar larval brains.…”
Section: Smph Activity Of 2% Nacl Extracts Derived From Brains Of Thrmentioning
confidence: 92%
“…), and Vanessa cardui L., Vanessa indica Herbst and Nymphalis xanthomelas japonica Esper, which do not exhibit seasonal polyphenism (Tanaka et al . ) following a Polygonia female short‐day (SD) pupal assay to detect SMPH activity (Endo et al . ).…”
Section: Smph Activity Of 2% Nacl Extracts Derived From Brains Of Thrmentioning
confidence: 99%
See 1 more Smart Citation